Aromaticity and sterics control whether a cationic olefin radical is resistant to disproportionation. Issue 16 (7th April 2020) - Messelberger, Julian; Grünwald, Annette; Goodner, Stephen J.; Zeilinger, Florian; Pinter, Piermaria; Miehlich, Matthias E.; Heinemann, Frank W.; Hansmann, Max M.; Munz, Dominik
Abstract : Only sterics and aromaticity control whether radical olefin cations are stable. Abstract : We elucidate why some electron rich-olefins such as tetrathiafulvalene (TTF) or paraquat (1, 1′-dimethyl-4, 4′-bipyridinylidene) form persistent radical cations, whereas others such as the dimer of N, N ′-dimethyl benzimidazolin-2-ylidene (benzNHC) do not. Specifically, three heterodimers derived from cyclic (alkyl) (amino) carbenes (CAAC) with N, N ′-dimethyl imidazolin-2-ylidene (NHC), N, N ′-dimethyl imidazolidin-2-ylidene (saNHC) and N -methyl benzothiazolin-2-ylidene (btNHC) are reported. Whereas the olefin radical cations with the NHC and btNHC are isolable, the NHC compound with a saturated backbone (saNHC) disproportionates instead to the biscation and olefin. Furthermore, the electrochemical properties of the electron-rich olefins derived from the dimerization of the saNHC and btNHC were assessed. Based on the experiments, we propose a general computational method to model the electrochemical potentials and disproportionation equilibrium. This method, which achieves an accuracy of 0.07 V (0.06 V with calibration) in reference to the experimental values, allows for the first time to rationalize and predict the (in)stability of olefin radical cations towards disproportionation. The combined results reveal that the stability of heterodimeric olefin radical cations towards disproportionation is mostly due to aromaticity. In contrast, homodimeric radical cations are in principle isolable, if lacking steric bulk in the 2, 2′ positions of the heterocyclic monomers. Rigid tethers increase accordingly the stability of homodimeric radical cations, whereas the electronic effects of substituents seem much less important for the disproportionation equilibrium.